2017
DOI: 10.1002/jssc.201601013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabonomic analysis of heart tissue from isoproterenol-induced myocardial infarction rat based on reversed-phase and hydrophilic interaction chromatography coupled to mass spectrometry

Abstract: We aim to describe the metabonomic characteristics of myocardial infarction rats. High-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was utilized to develop a metabonomic method of the heart homogenates of myocardial infarction rats. Hydrophilic interaction chromatography allows the analysis of high polar metabolites, providing complementary information to reversed-phase liquid chromatography. We combined reversed phase and hydrophilic interaction chromatographic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Increased GSSG levels were also observed by Liu and colleagues, who concluded that isoproterenol can inhibit both enzymes in the heart, leading to GSSG accumulation (Liu et al, 2013). However, Sun et al demonstrated the depletion of glutathione levels as an isoproterenol effect in rat hearts, in disagreement with was observed in the present study (Sun et al, 2017). Furthermore, the average ratio between reduced glutathione and oxidized glutathione (GSH/GSSG) under normal conditions, is 10:1 or greater, depending on the cell type, and an altered ratio is indicative of oxidative stress.…”
Section: Discussioncontrasting
confidence: 75%
“…Increased GSSG levels were also observed by Liu and colleagues, who concluded that isoproterenol can inhibit both enzymes in the heart, leading to GSSG accumulation (Liu et al, 2013). However, Sun et al demonstrated the depletion of glutathione levels as an isoproterenol effect in rat hearts, in disagreement with was observed in the present study (Sun et al, 2017). Furthermore, the average ratio between reduced glutathione and oxidized glutathione (GSH/GSSG) under normal conditions, is 10:1 or greater, depending on the cell type, and an altered ratio is indicative of oxidative stress.…”
Section: Discussioncontrasting
confidence: 75%
“…(Spagou et al 2010 ; Tang et al 2016 ). Indeed the combination of RPLC and HILIC has begun to be used as standard practice where comprehensive profiles are required (Contrepois et al 2015 ; Gika et al 2008 ; Paris et al 2016 ; Sun et al 2017 ). Other modes of separation employed in the analysis of extremely polar compounds have proven to be reliable and reproducible, but in the case of e.g., normal phase and ion-exchange chromatography, compatibility issues with mass spectrometry and electrospray ionisation, due to the solvents and additives used, have made these techniques less attractive than HILIC for high throughput metabolomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase in dhSPh measured by LC/MS was strongly supported by the heightened SPT activity of chorionic arteries of PE patients. Increased dhSph levels have been associated with cellular lipotoxicity, in the context of diabetes and neurodegenerative and cardiovascular diseases [47][48][49], and most likely also contributes to the onset of the endothelial dysfunction of the chorionic arteries.…”
Section: Discussionmentioning
confidence: 99%